Comparative engine testing of Bio-CNG and Gasoline: Performance and emission impacts in a 175 CC engine - Sangam Bhusal; Yudeep Poudel; Srijan Bastakoti; Sachin Adhikari; Rupesh Lal Karn; Laxman Palikhel (Journal of Innovations in Engineering Education, 2024)
Bio-CNG has emerged as a potential replacement for conventional fossil fuels used in road vehicles, a major source of global air pollution. This research aimed to perform comparative performance and emission analysis under various conditions to observe its viability. A Bajaj, 175 CC powered gasoline, 4-stroke, and carbureted engine was chosen and converted to the bi-fuel system that operates either with gasoline or bio-CNG using an electronically controlled solenoid valve. The engine power and traction forces were measured under the road's 0o, 4o, and 8o inclination at no load and 5kW load coefficients. Vehicle exhaust emission levels (CO, CO2, HC, and lambda) were measured at the idle rpm of the engine (1240 RPM for petrol and 1022 RPM for bio-CNG). The experimental data from the chassis dynamometer revealed significant reductions in power and traction force under various conditions. Furthermore, emissions analysis from exhaust gas analyzer showed remarkable reductions of 98% for CO and 89% for HC, but there was a 16.67% increase in CO2 levels. This research provides insights into the potential benefits and challenges of bio-CNG conversion for small-engine vehicles and suggests possible measures to improve the performance of converted vehicles.